2019
DOI: 10.26452/ijrps.v10i3.1459
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization review of corticosteroids in a tertiary care hospital of Salem District, Tamilnadu, India

Abstract: Corticosteroids are widely used compounds for allergic reactions, autoimmune diseases, inflammatory conditions, hormone replacement therapy etc. Hence, with widespread use and actions, these have several interactions with drugs and diseases. The purpose of this study was to obtain information about Corticosteroids prescribing and utilization pattern, to understand the prescribing behaviour of physicians and to identify drug interactions. A retrospective observational study was conducted in the department of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A drug utilization study revealed majority of patients (66%) were prescribed steroids for respiratory illness. (Balasubramanian et al, 2019) This study was conducted in a tertiary care hospital and across various departments and has captured almost all the diagnoses where glucocorticoids have been prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…A drug utilization study revealed majority of patients (66%) were prescribed steroids for respiratory illness. (Balasubramanian et al, 2019) This study was conducted in a tertiary care hospital and across various departments and has captured almost all the diagnoses where glucocorticoids have been prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…The DUE studies have a promising impact locally and internationally as they are relentlessly used indicators of the healthcare system. Prescribing patterns are frequently utilized technique to assess the agreement of doctors who prescribe according to standard treatment guidelines as well as rational prescribing practices (Balasubramanian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%